Mechanical and tribological behaviour of titanium boride coatings processed by thermochemicals treatments. (2nd January 2021) - Khater, Mohammed Amine; Bouaziz, Sabik Abdelhadi; Garrido, M. A.; Poza, P.
ABSTRACT: The present work aims to study the mechanical and tribological properties of titanium boride layer processed by a thermochemical boriding treatment, which was carried out in a salt bath consisting of 70% borax and 30% silicon carbide. The boriding temperatures were 850°C, 950°C and 1000°C with holding times of 2, 4, 6 and 8 h. The analysis by optical and scanning electron microscopy and X-ray diffraction method confirmed the formation of a single-phase layer of titanium diboride (TiB2 ) in the substrate surface. The thickness of the boride layer increases with time and temperature, reaching a maximum value of 50 μm. The microhardness was evaluated for the substrate and the boride layer. Additionally, nanomechanical characterization of the layer was carried out by nanoindentation tests. The influence of this treatment on the coefficient of friction and on the wear rate in a simulated medium of the body fluid was also studied.